Meningioma: A Literature Review - Trisna Ayu Kurnia Putri; Lale Maulin Prihatin; Bambang Priyanto (Jurnal Biologi Tropis, 2023)
Meningioma is the most common type of the central nervous system tumor. South East Asia is the third highest cases of central nervous system tumor with 190,376 cases every year. The majority of meningioma cases are benign, although few of the cases requires a lot more significant treatment in order to survive. Although meningiomas with complicated histopathology and/or in tricky locations can be challenging for surgeons to treat. The earlier we detect and handle brain tumor, the better the prognosis outcome for the patient. Method used in this paper is literature review. Review made by finding and curating literatures regarding meningioma on online databases such as PubMed, Google Scholar, and Proquest. This paper summarizes the current epidemiology, etiology, histopathology, pathology, diagnosis, and the current treatments available for meningioma.